Creating Clean Air Spaces During Wildland Fire Smoke Episodes: Web Summit Summary - Davison, Gilliane; Barkjohn, Karoline K.; Hagler, Gayle S. W.; Holder, Amara L.; Coefield, Sarah; Noonan, Curtis; Hassett-Sipple, Beth (Frontiers in Public Health, 2021)
Effective strategies to reduce indoor air pollutant concentrations during wildfire smoke events are critically needed. Worldwide, communities in areas prone to wildfires may suffer from annual smoke exposure events lasting from days to weeks. In addition, there are many areas of the world where high pollution events are common and where methods employed to reduce exposure to pollution may have relevance to wildfire smoke pollution episodes and vice versa. This article summarizes a recent virtual meeting held by the United States Environmental Protection Agency (EPA) to share research, experiences, and other information that can inform best practices for creating clean air spaces during wildland fire smoke events. The meeting included presentations on the public health impacts of wildland fire smoke; public health agencies’ experiences and resilience efforts; and methods to improve indoor air quality, including the effectiveness of air filtration methods (e.g., building heating ventilation and air conditioning (HVAC) systems and portable, free-standing air filtration systems). These presentations and related research indicate that filtration has been demonstrated to effectively improve indoor air quality during high ambient air pollution events; however, several research questions remain regarding the longevity and maintenance of filtration equipment during and after smoke events, effects on the pollution mixture, and degree to which adverse health effects are reduced.